INPP5E and Coordination of Signaling Networks in Cilia - Zhang, Renshuai; Tang, Jianming; Li, Tianliang; Zhou, Jun; Pan, Wei (Frontiers in Molecular Biosciences, 2022)
Primary cilia are ubiquitous mechanosensory organelles that specifically coordinate a series of cellular signal transduction pathways to control cellular processes during development and in tissue homeostasis. Defects in the assembly or function of primary cilia have been shown to be associated with a large range of developmental disorders and diseases called ciliopathies. Inositol polyphosphate-5-phosphatase E (INPP5E) is an inositol polyphosphate 5-phosphatase that is localized on the ciliary membrane by anchorage via its C-terminal prenyl moiety and hydrolyzes both phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2) and PtdIns(3,4,5)P3, leading to changes in the phosphoinositide metabolism, thereby resulting in a specific phosphoinositide distribution and ensuring proper protein trafficking and Hh signaling in primary cilia. In addition, INPP5E also works synergistically with cilia membrane-related proteins by playing key roles in the development and maintenance of cilia. The mutation of INPP5E will cause deficiency of primary cilium signaling transduction, ciliary instability and ciliopathies. Here, we present an overview of the role of INPP5E and its coordination of signaling networks in primary cilia.